2021
DOI: 10.1038/s41380-021-01243-6
|View full text |Cite|
|
Sign up to set email alerts
|

Cortical organoids model early brain development disrupted by 16p11.2 copy number variants in autism

Abstract: Reciprocal deletion and duplication of the 16p11.2 region is the most common copy number variation (CNV) associated with autism spectrum disorders. We generated cortical organoids from skin fibroblasts of patients with 16p11.2 CNV to investigate impacted neurodevelopmental processes. We show that organoid size recapitulates macrocephaly and microcephaly phenotypes observed in the patients with 16p11.2 deletions and duplications. The CNV dosage affects neuronal maturation, proliferation, and synapse number, in … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
51
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(65 citation statements)
references
References 125 publications
6
51
0
Order By: Relevance
“…Downregulated genes were implicated in neuron projection morphogenesis, neuron cell-cell adhesion, axon development and other terms implicating neurite process assembly and neuron-to-neuron interaction (Figure 6B). This result is consistent with a recent study which identified defects in neuronal migration in 16p11.2 hemideletion hCOs 82 . Furthermore, upregulated genes were implicated in synaptic-relevant processes such as signal transmission and neurotransmitter biosynthesis and transport (Figure 6B, Table S4).…”
Section: Pathway and Gene-disease Network Analysis In Hemideletion Patient Linessupporting
confidence: 94%
See 1 more Smart Citation
“…Downregulated genes were implicated in neuron projection morphogenesis, neuron cell-cell adhesion, axon development and other terms implicating neurite process assembly and neuron-to-neuron interaction (Figure 6B). This result is consistent with a recent study which identified defects in neuronal migration in 16p11.2 hemideletion hCOs 82 . Furthermore, upregulated genes were implicated in synaptic-relevant processes such as signal transmission and neurotransmitter biosynthesis and transport (Figure 6B, Table S4).…”
Section: Pathway and Gene-disease Network Analysis In Hemideletion Patient Linessupporting
confidence: 94%
“…Most of the transcriptional changes we found in hemideletion lines were specific to neuronal cell types, and gene enrichment analysis showed neuronal maturation and synaptic function relevant signatures in hemideletion patients. Despite the apparent methodological differences, the overall finding of increased neuronal maturation in hemideletions was similar to a recent study using 3D brain organoids 82 . We observed minimal changes in hemiduplication lines.…”
Section: By Modelling 16p112 Cnvs With Patient-derived Hcos In Combination Withsupporting
confidence: 85%
“…So far, the pathological characteristics of neuropsychiatric disorders have been extensively recapitulated in vitro in the research of human brain organoids ( Figure 2 , right panel). The consistency of in vivo and in vitro cellular results demonstrated the feasibility of the in vitro brain organoids as an experimental model of neuropsychiatric disorders [ 62 , 63 ]. Multi-omics analysis demonstrated that cerebral organoids derived from human PSCs in vitro could recapitulate cerebral cortical development corresponding to the molecular level of before 16 weeks post-conception in vivo [ 64 ].…”
Section: Recapitulating Neuropsychiatric Disorders With Brain Organoidsmentioning
confidence: 98%
“…Due to a lack of understanding of disease mechanisms, there are no specific treatments for NDDs caused by CNVs. Evidence indicates that the loss/gain of certain genes within a CNV, known as 'genetic drivers', are the major cause of neurological deficits [3][4][5][6][7][8][9] ; however, genetic mechanisms outside of the CNV region, as well as pleiotropic and polygenic contributions, also play a role [10][11][12] . Given that multiple genes are located within a CNV, studies have focused on genetic drivers to identify relevant disease mechanisms and molecular targets for potential intervention.…”
Section: Introductionmentioning
confidence: 99%